Muscular Sarcocystosis in Sheep Associated With Lymphoplasmacytic Myositis and Expression of Major Histocompatibility Complex Class I and II. Issue 2 (March 2020) - Pagano, Teresa Bruna; Prisco, Francesco; De Biase, Davide; Piegari, Giuseppe; Maurelli, Maria Paola; Rinaldi, Laura; Cringoli, Giuseppe; Papparella, Serenella; Paciello, Orlando
Sarcocystosis is a protozoal disease affecting a wide range of animals. The aims of this study were to characterize the following in sheep: (1) the muscle pathology in Sarcocystis infection, (2) the inflammatory infiltrate and its relationship to severity of infection, and (3) immune markers expressed by parasitized muscle fibers and parasitic cysts. Skeletal muscle samples from 78 sheep slaughtered in southern Italy were snap frozen and analyzed by histopathology, immunohistochemistry, and immunofluorescence. Polymerase chain reaction (PCR) and sequencing were used for Sarcocystis species identification. All 40 muscle samples tested were PCR-positive for Sarcocystis tenella. Histologically, cysts were identified in 76/78 cases (97%), associated with an endomysial infiltrate of lymphocytes and plasma cells. The T cells were predominantly CD8+, with fewer CD4+ or CD79α+ cells. Eosinophils were absent. Notably, sarcolemmal immunopositivity for major histocompatibility complex (MHC) I and II was found in 76/78 cases (97%) and 75/78 cases (96%), respectively, both in samples with and in those without evident inflammatory infiltrate. The number of cysts was positively correlated with inflammation. In addition, MHC I was detected in 55/78 cyst walls (72%), and occasionally co-localized with the membrane-associated protein dystrophin. The findings suggest that muscle fibers respond to the presence of cysts by expression of MHC I and II. The possible role of MHC I and II in the inflammatory response and on the cyst wall is also discussed.